Risk Factors Regarding the Incomplete Vaccination Schedule in Children Under 5 Years - Andrés Sebastián Guevara Pabón; Erika Marcela León Revelo; Leonel Gerardo Ruano Yarpaz (Medisur)
Foundation: non-compliance with the vaccination program is one of the major health problems that affects Ecuador. It is the cause of thousands of deaths, especially of children under 5 years of age. Objective: to describe some of the factors associated with non-compliance with the vaccination schedule in children under 5 years of age at the Health Center, El Priorato, Ibarra, Ecuador. Method: a descriptive and cross-sectional study was carried out with patients from the Health Center, El Priorato, in the city of Ibarra, Imbambura province, Ecuador, in the period from January to December 2023. The universe was comprised of 110 parents of minor children. of 5 years. Sociodemographic variables were studied and descriptive statisticians were used. Results: the predominant age group was parents between 18 and 35 years old with 73 patients for 66.3 %. The male sex predominated with 56 patients (50.9 %). The most reported marital status was: married, with 42 patients (38.1 %). The most frequent distance to the Health Center was: 1 hour, in the case of 58 patients (52.7 %). The main causes of abandonment were: lack of financial means, situation of 49 patients (44.5 %) and ignorance of the vaccination date in 40 patients for 36.3% of the total. Conclusions: lack of economic resources and ignorance of vaccination dates were causes associated with non-compliance with the vaccination schedule of children under 5 years of age.